Evaluation of Current Status of Newly Established Model Pharmacies in Bangladesh - Mondal, Shadhan Kumar; Chowdhury, Sabiha; Ganguly, Amlan; Faroque, ABM (Dhaka University Journal of Pharmaceutical Sciences, 2021)
Pharmaceutical sector of Bangladesh has developed profoundly after promulgation of the Drugs (Control) Ordinance, 1982. However, the health sector has not been equally developed because of lack of wellequipped drug management system and much needed patient counseling. The presence of adulterated, counterfeit and substandard drugs and the sale of drugs at high prices than the maximum retail price have also been the major problems here. The recent introduction of model pharmacies is supposed to be a hope for the people to get safe medicines at a reasonable cost. The aim of the present study was to find out the current scenario of model pharmacies in Bangladesh and to propose modern and alternative systems that could be applied in model pharmacies for better healthcare management and patient compliance. Thus, the current status of model pharmacies of Bangladesh has been evaluated using a survey-based analysis which utilized a pre-set questionnaire. The survey was conducted on 90 model pharmacies in seven districts of Bangladesh (Level 1 categorized by the Directorate General of Drug Administration, Government of the People’s Republic of Bangladesh). The results revealed that the infrastructure of the model pharmacies should be improved further. Only 33% of the model pharmacies have sitting facilities and 51% of them have washroom facilities for the waiting patients. It was found that despite all the model pharmacies (100%) should have at least 1 A-grade pharmacist in each of them, i.e. a pharmacy graduate registered with the Pharmacy Council of Bangladesh under the Pharmacy Ordinance 1976, but pharmacists were found to be present in only 26% of pharmacies during the visit. Amongst the pharmacists, 98% showed satisfaction with the decision of compulsory engagement of A-grade pharmacists in all the model pharmacies. Defying the obligatory provisions, only 38% model of pharmacies keep the required records of sold drugs. It was pleasing to observe that no physician’s sample of medicines was sold in any model pharmacies. The medicines storage facilities in controlled temperature was found in all the model pharmacies. But the A-grade pharmacists were not available in the pharmacies during holidays. It is opined that modern and ICT based techniques can be applied to modify the model pharmacies for better patient care and patient management. Dhaka Univ. J. Pharm. Sci. 20(1): 1-10, 2021 (June)